Anthropogenic monoterpenes aggravating ozone pollution. Issue 9 (31st May 2022) - Wang, Haichao; Ma, Xuefei; Tan, Zhaofeng; Wang, Hongli; Chen, Xiaorui; Chen, Shiyi; Gao, Yaqin; Liu, Ying; Liu, Yuhan; Yang, Xinping; Yuan, Bin; Zeng, Limin; et al.
Abstract: Monoterpenes have been known to have a critical influence on air quality and climate change through their impact on the formation of fine particles. Here we present field evidence that monoterpene oxidations largely enhanced local ozone production in a regional site in eastern China. The observed monoterpene was most likely from biomass burning rather than biogenic emissions, as indicated by the high correlation with CO at night-time, and the observed ratio of these two species was consistent with previously determined values from biomass burning experiments. Fast monoterpene oxidations were determined experimentally based on direct radical measurements, leading to a daily ozone enhancement of 4–18 parts per billion by volume (ppb), which was 6%–16% of the total ozone production, depending on the speciation of monoterpenes. It demonstrates that the previously overlooked anthropogenic monoterpenes make an important contribution to O3 production in eastern China. The role could possibly be important at similar locations across China and other parts of the world that are characterized by massive emissions, especially where there are high NO x levels. Our results highlight that anthropogenic monoterpenes should be taken into account when proceeding with the coordinated mitigation of O3 and particulate matter pollution. Abstract : The previously overlooked anthropogenic monoterpene emission effectively worsens ozone pollution in eastern China, accounting for 6-16% of the total ozone production.